1992
DOI: 10.1523/jneurosci.12-05-01896.1992
|View full text |Cite
|
Sign up to set email alerts
|

On the role of nerve growth factor in the development of myelinated nociceptors

Abstract: We have previously demonstrated that administration of antisera against NGF (anti-NGF) can have profound effects on developing primary afferents (Ritter et al., 1991). Chronic administration of anti-NGF to rats beginning on the day of birth results in a severe depletion of cutaneous A delta high-threshold mechanoreceptors (HTMRs) from the sural nerve. Here we have carried out further experiments in order to define the period of time over which this change in the cutaneous afferent population can be produced, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(102 citation statements)
references
References 40 publications
6
96
0
Order By: Relevance
“…Because no specific marker for heat-sensitive AM fibers is available at this time, we cannot exclude the possibility that there may be selective cell death of heat-sensitive AM fibers. However, we favor the explanation that the heat-sensitive AM fibers in p75Ϫ/Ϫ mice underwent a phenotype switch, because other studies have shown that AM nociceptors undergo a permanent phenotype switch to D-hair receptors after postnatal treatment with antibodies that neutralizes endogenous NGF (Ritter et al, 1991;Lewin et al, 1992). Additional evidence from our laboratory suggests that the ligand responsible for the change in AM fibers in p75Ϫ/Ϫ mice is NGF, because NT-3, BDNF, or NT-4 are not required for the survival or function of AM nociceptors (Koltzenburg et al, 1995;Airaksinen et al, 1996;Stucky et al, 1996).…”
Section: Specific Functionally Defined Subpopulations Of Sensory Neurmentioning
confidence: 83%
“…Because no specific marker for heat-sensitive AM fibers is available at this time, we cannot exclude the possibility that there may be selective cell death of heat-sensitive AM fibers. However, we favor the explanation that the heat-sensitive AM fibers in p75Ϫ/Ϫ mice underwent a phenotype switch, because other studies have shown that AM nociceptors undergo a permanent phenotype switch to D-hair receptors after postnatal treatment with antibodies that neutralizes endogenous NGF (Ritter et al, 1991;Lewin et al, 1992). Additional evidence from our laboratory suggests that the ligand responsible for the change in AM fibers in p75Ϫ/Ϫ mice is NGF, because NT-3, BDNF, or NT-4 are not required for the survival or function of AM nociceptors (Koltzenburg et al, 1995;Airaksinen et al, 1996;Stucky et al, 1996).…”
Section: Specific Functionally Defined Subpopulations Of Sensory Neurmentioning
confidence: 83%
“…Other methods, such as derivation via neurospheres 7,8 , rely on the mitogenic properties of GFs such as basic fibroblast growth factor (bFGF), epidermal growth factor (EGF) and platelet-derived growth factor (PDGF) for OPC expansion. Similarly, using postnatal (P5-10) mice for DRGNs avoids the requirement of supplementing the culture media with nerve growth factor (NGF), a neurotrophic factor required for the in vitro survival of embryonic DRGNs 9,10 . It is of interest to avoid using NGF as it negatively influences the myelinating capacity of OLs when cultured with DRGNs 4 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…This postnatal reduction in the percentage of TrkA ϩ neurons occurs gradually over 3 weeks (postnatal day 1 [P1] to P21), coinciding with the critical period during which alteration of neurotrophins can permanently alter the physiology of neonatal dorsal root and trigeminal ganglion neurons (19,25). Downregulation of TrkA by IB4-binding neurons results in differences in expression profiles and signaling cascades in response to certain classes of stimuli (33,39,53).…”
Section: Discussionmentioning
confidence: 99%